STUDY OF THE SORPTION ACTIVITY OF ENTEROSORBENT ON THE BASIS OF MONTMORILLONITEAGAINST THE E.coli ENTEROTHOXIN ON THE MODEL OF ISOLATED LOOPES OF THE INTESTINE - A. N. TISHIN; M. V. POKROVSKII; O. M. TISHINA; L. N. SERNOV; V. J. PROVOTOROV; E. A. BESKHMELNITSYNA (Кубанский научный медицинский вестник, 2017)
Aim. To study the sorption activity of enterosorbent based on montmorillonite under the laboratory cipher of Crim_04 against E.coli enterotoxin in vivo.Material and Methods. Isolated loops of the small intestine were formed in laboratory rats under anesthesia, and E. coli toxin was injected into the control loops at a dose of 2 μg/loop. The enterosorbent under the code Crim_04 in the form of water suspensions with concentrations of 50 mg/ml, 100 mg/ml and 200 mg/ml was injected into the lumen of the loops with toxin. After 4 hours, the expression of the fluid in the lumen of the intestine and its inhibition by the enterosorbent were evaluated. Comparison was Smekta.Results. The introduction of toxin into the lumen of the gut caused an increased fluid yield, the dilatation index for the control loops was 112,7±1,2 mg/cm versus 27,4±0,4 mg / cm in intact loops. The enterosorbent under the Crim_04 cipher exhibited a dose-dependent inhibitory effect on the fluid outlet into the lumen of the gut, at a concentration of 200 mg/ml, the dilation index was 31,6±0,8 mg / cm, inhibiting the fluid yield by 95,1%. This effect is confirmed morphologically, the morphometric parameters when using enterosorbent under the Crim_04 cipher are close to the level of intact loops.Conclusion. The montmorillonite-based enterosorbent under the laboratory cipher Crim_04 has a high sorption activity against the thermolabile cholera-like E. coli enterotoxin on the isolated bowel loop model.